Особливості розслідування злочинів, скоєних медичним працівником - Топчій, Василь Васильович (Одеський державний університет внутрішніх справ МВС України, 2018)
Стаття присвячена розробці криміналістичної характеристики розслідування злочинів, скоєних медичним працівником, встановленню особливостей проведення окремих слідчих дій під час розслідування медичних злочинів, розробці рекомендацій щодо висунення версій і планування розслідування, визначення тактичних особливостей проведення слідчих дій, розкриття особливостей застосування спеціальних знань під час розслідування злочинів, скоєних під час надання медичної допомоги.

The article is devoted to the development of the forensic character of the investigation of crimes committed by a medical worker, to the establishment of peculiarities of conducting separate investigative actions in the investigation of medical crimes, to the development of recommendations for the introduction of versions and planning of the investigation, to the definition of tactical features of conducting investigative actions, to disclosure of the peculiarities of the use of special knowledge during the investigation of crimes committed in the provision of medical care. Crimes against human life and health committed by medical workers can be defined as socially dangerous, criminal acts of medical workers carried out by them in the course of their professional activities by not providing or improperly providing medical and medical care to patients who have resulted in death or substantial damage to the health of one or more patients. Forensic characteristics of crimes against human life and health committed by healthcare professionals in the course of their professional activities and which have caused harm to people’s life and health, facilitates the organization of investigation of crimes of this group and a systematic description, which includes information about the main criminalistic elements of the crime. Among the circumstances that are to be established in the investigation of criminal offenses of professional activities by medical workers, there is the establishment of a violation of the rules governing this activity. The investigation is carried out by conducting investigative (search) actions: an overview of the place of the event, the detection and interrogation of its witnesses, victims, organization of inspection of institutions, inspections of certain aspects of their activities with the help of specialists, study documents and the use of data contained in them in the process of proof, interrogation of medical staff, appointment and conduct of forensic and other medical examinations.
Keywords: злочини; скоєні медичним працівником; розслідування злочинів у медичній сфері; слідчі дії; особливості розслідування злочинів; crimes committed by a medical officer; investigation of crimes in the medical sphere; investigative actions; peculiarities of investigation of crimes